Tacit knowledge and firm performance relationship. The role of product innovation and the firm level capabilities - López-Cabarcos, M. Ángeles; Srinivasan, Suresh; Göttling-Oliveira-Monteiro, Sérgio; Vázquez-Rodríguez, Paula (Journal of Business Economics and Management, 2019)
Based on knowledge-based theory of organizational capabilities and dynamic capabilities theory, this paper tries to establish the linkages between tacit knowledge resources, its integration into firm level capabilities, product innovation and firm performance. In this way, the paper analyses the relationships between some of the most relevant variables to the organizations in order to remain competitive. The conceptual model is tested using a sample of organizations in the industrial sector, using SEM and hierarchical regression analysis. Results show a positive relationship between tacit knowledge and firm performance, tacit knowledge and product innovation, and product innovation and firm performance. A partial mediating effect of product innovation on the tacit knowledge firm performance relationship is established. Also, technical capabilities have a moderator effect on tacit knowledge firm performance relationship. At the end of the paper managerial implications are commented, as well directions for future studies.